Circadian Oscillations in the Murine Preoptic Area Are Reset by Temperature, but Not Light - Díaz, Nicolás M.; Gordon, Shannon A.; Lang, Richard A.; Buhr, Ethan D. (Frontiers in Physiology, 2022)
Mammals maintain their internal body temperature within a physiologically optimal range. This involves the regulation of core body temperature in response to changing environmental temperatures and a natural circadian oscillation of internal temperatures. The preoptic area (POA) of the hypothalamus coordinates body temperature by responding to both external temperature cues and internal brain temperature. Here we describe an autonomous circadian clock system in the murine ventromedial POA (VMPO) in close proximity to cells which express the atypical violet-light sensitive opsin, Opn5. We analyzed the light-sensitivity and thermal-sensitivity of the VMPO circadian clocks ex vivo. The phase of the VMPO circadian oscillations was not influenced by light. However, the VMPO clocks were reset by temperature changes within the physiological internal temperature range. This thermal-sensitivity of the VMPO circadian clock did not require functional Opn5 expression or a functional circadian clock within the Opn5-expressing cells. The presence of temperature-sensitive circadian clocks in the VMPO provides an advancement in the understanding of mechanisms involved in the dynamic regulation of core body temperature.